Faktor Penghambat Minat Pemustaka Dalam Pemanfaatan Pelayanan Referensi UPT Perpustakaan Universitas Riau - Hasnidar (Jurnal Gema Pustakawan, 2013)
This study entitled "Factors Inhibiting the Use of Interest Visitors Reference Services Unit Riau University Library". Research object is a reference service and lack of interest Visitors inhibiting factor in the utilization of reference services. The goal of research to find out how to use reference services of Riau University Library UPT and inhibiting factors Visitors interest in reference services. The research method used is descriptive qualitative method. Study sample as many as 104 people who obtained 10% of the population.The results showed that: (1). Utilization of library reference services in UPT can be seen from Riau University, (a). The volume of traffic that varies 1-2 times a week 40 people (38.5%), 3-4 times a week, 38 people (36.5%), more than 5 times a week 14 people (13.5%). (b). Purpose of visit 51 people (49.1%) respondents stated that the reference service is the ultimate reference service. (2). Inhibiting factor Visitors interest in the utilization of reference services can be viewed in terms of availability of collections, the diversity of the subject / title of the collection, the diversity of the collection, the relevance of collections to the needs, currency collection, good service and the availability of search.